2014
DOI: 10.1088/0963-0252/23/1/015015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of air diffusion on the OH radicals and atomic O distribution in an atmospheric Ar (bio)plasma jet

Abstract: Treatment of samples with plasmas in biomedical applications often occurs in ambient air. Admixing air into the discharge region may severely affect the formation and destruction of the generated oxidative species. Little is known about the effects of air diffusion on the spatial distribution of OH radicals and O atoms in the afterglow of atmospheric-pressure plasma jets. In our work, these effects are investigated by performing and comparing measurements in ambient air with measurements in a controlled argon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 43 publications
(61 reference statements)
2
26
0
Order By: Relevance
“…It has been proposed that the plasma generated in Helium with O 2 and H 2 O is rich not only in O, O 2 *, and O 3 but also in OH and H 2 O 2 . [49][50][51][52] By utilizing different ROS scavengers, we found that H 2 O 2 played an important role in the cytotoxic effects on Bel7402 cells. H 2 O 2 is moderately reactive and is relatively long-lived molecules, 53 and it is also the only ROS that could diffuse over membrane with large distances within the cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the plasma generated in Helium with O 2 and H 2 O is rich not only in O, O 2 *, and O 3 but also in OH and H 2 O 2 . [49][50][51][52] By utilizing different ROS scavengers, we found that H 2 O 2 played an important role in the cytotoxic effects on Bel7402 cells. H 2 O 2 is moderately reactive and is relatively long-lived molecules, 53 and it is also the only ROS that could diffuse over membrane with large distances within the cells.…”
Section: Discussionmentioning
confidence: 99%
“…When a plasma jet propagates in ambient air, the diffusion of the ambient air will affect the reactive species generation. There are two ways to control the diffusion of the ambient air [277][278][279][280][281][282]. One way is by placing the plasma jet inside a sealed container, which is filled with the desired gas.…”
Section: Effect Of Diffusion Of Shielding Gas On O Productionmentioning
confidence: 99%
“…The observed oxygen incorporation is due to the admixture of air in the plasma effluent. This leads to a higher yield of OH and O in the core of the discharge when the discharge is operating in ambient air [16]. Due to the recombination processes of OH and O with intrusions of nitrogen and oxygen molecules from the surrounding air, only a low amount of these species will reach the LDPE surface at higher distances, resulting into less hydrophilic surfaces and lower O/C ratios.…”
Section: Influence Of the Distance Between The Capillary And The Foilmentioning
confidence: 99%